3D Atomic-Scale Insights into Anisotropic Core-Shell-Structured InGaAs Nanowires Grown by Metal-Organic Chemical Vapor Deposition - Qu, Jiangtao (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.